Penerapan Metode Economic Order Quantity (EOQ) Untuk Meningkatkan Efisiensi Pengendalian Persediaan Bahan Baku Pada CV Simka Jaya - Pesta Gultom; Eliajar Julius Otniel Perangin-Angin; Friska Canserina Aritonang (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Stock management is an important element in running a business, especially in the manufacturing sector, which plays a major role in providing raw materials so that the production process can run smoothly. Improper inventory handling can result in wasted costs, both in terms of storage and procurement, and can lead to the danger of raw material shortages that have the potential to disrupt smooth production. This study aims to disseminate how effective CV Simka Jaya, a company engaged in the manufacture of koko clothing, is in managing its raw material stock through the Economic Order Quantity (EOQ) approach. This EOQ method determines the optimal purchase amount to reduce inventory costs, by including Safety Stock and Reorder Point analysis as an effort to address orders in demand and potential delays in delivery.